Molecular characterization and interactome analysis of aerolysin (aer) gene from fish pathogen Aeromonas veronii: The pathogenicity inferred from sequence divergence and linked to histidine kinase (cheA). Issue 4 (7th February 2019) - Foysal, Md Javed; Momtaz, Farhana; Ali, Md Hazrat; Siddik, Muhammad A. B.; Chaklader, Md Reaz; Rahman, Md Mahbubur; Prodhan, Md Shamsul Haque; Cole, Anthony
Abstract: Aerolysin ( aer ) is one of the most important and abundant virulence factors in the infection of fish by Aeromonas veronii . A comprehensive study on the molecular characterization and pathogenicity of the aer gene from 34 A. veronii isolates from diseased carp and catfish was carried out and its interactome was analysed to observe the functional correlations between aer and other proteins within the A. veronii network. The PCR‐based amplification of aer from the 34 isolates of A. veronii showed more aer ‐positive isolates from catfish with a high pathogenic potential in the in vivo challenge test than the carp fish. The analysis of aer gene sequence from challenged fish revealed significant sequence divergence according to the types and geographical distribution of the fish. The networking analysis of aer from the model A. veronii B565 revealed histidine kinase ( che A) as the most functional interacting partner. The study of the interaction between aer from the experimental A. veronii and che A demonstrated that the A chain of che A plays a more important role than the corresponding B chain during contact, and a linker sequence of 15 residues controlled the entire interaction process. Therefore, che A could be an excellent drug target for controlling A. veronii infection of fish.